Arbitrase sebagai Solusi Sengketa Bisnis : Menakar Keunggulan dan Tantangan Berdasarkan Undang-Undang No. 30 Tahun 1999 Tentang Arbitrase dan Alternatif Penyelesaian Sengketa - Faizul Idris; Nandang Sambas (Pusat Riset dan Inovasi Nasional, 2025)
Arbitration is an alternative methode of dispute resolution for business conflicts, as regulated in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. This study aims to analyze the advantages and challenges of arbitration in resolving business disputes in Indonesia. The findings indicate that arbitration offers several key advantages, including a faster process, more controlled costs, confidentiality, and final and binding decisions. However, its implementation still faces challenges, such as a lack of understanding among business actors regarding arbitration mechanisms, difficulties in enforcing arbitral awards, and, in some cases, higher costs compared to litigation in court. To optimize the role of arbitration, further socialization efforts, reforms in award enforcement, capacity building for arbitrators, and the simplification of regulations related to arbitration costs are necessary. With these measures, arbitration can become one of solution for resolving business disputes in Indonesia.